Data processing platform design and algorithm research of wearable sports physiological parameters detection based on medical internet of things. (1st December 2020) - Wu, Qinqin; Tang, Panyu; Yang, Maolin
Highlights: Physiological parameter detection in the data processing platform through the built-in algorithm. The physiological parameter array is obtained and transmitted to ZigBee network by platform. It can realize the remote and real-time information interaction between doctors and patients. Abstract: In this paper, the data processing platform for the detection of wearable Sports Physiological Parameters Based on the medical Internet of things can be connected with the network to build a medical Internet of things platform for remote monitoring of patients' lives, which can process physiological data in real time. Finally, the important physiological parameter array of human body is obtained and transmitted to ZigBee network in real time. If the patient needs further diagnosis, the collected data can also be sent to the home gateway through ZigBee and then sent to the telemedicine center through internwt for diagnosis by the doctor and the diagnosis results will be sent back to the patient. The data processing platform can realize the remote and real-time information interaction between doctors and patients.